Nouns Formed with -ism Suffix as a Type of Nominalization in Modern Russian Language (Proceedings of Southern Federal University. Philology, 2021)
Zhang Shuchun, Olga V. Kukushkina (Moscow, Russian Federation)In the article Russian nouns formed with -ism suffix, often containing borrowed roots from other Indo-European languages, are analyzed from the perspective of their syntactic function as nominalization. As nominalization regarded in linguistics as a type of pure syntactic transformation (or “syntactic derivation” according to the definition of Jerzy Kuryłowicz), the -ost’ suffix as a word-formational formant for syntactic derivation is well acknowledged and described. As a contrast, the studied group of nouns with -ism suffix is seldom associated with or regarded as deadjectival nominals in previous works and dictionaries. Our analysis based on explanatory and morpheme dictionaries has shown, the motivational correlation between nouns with -ism suffix and adjectives are described in multiple ways, often contrasted one another. For instance, -isms are described in the morpheme dictionary (Lopantin, Ulukhanov 2016) as deadjectival nouns, while in the Shvedova dictionary as non-derivatives, motivating adjectives of quality. In addition, the seme ‘quality’ is also described variously in the two dictionaries – directly or using synonyms with different formants. The analysis of word-usages of -isms was conducted with the corpus “Russian Newspapers of the End of the XX Century”, developed by the Laboratory for General and Computational Lexicology and Lexicography (Lomonosov Moscow State University). The analysis has shown that the diagnostic context automatically differentiate the usage of -isms as nominalizations are the dependent names of the “feature carrier”, which as a result of nominalization has been moved from the position of subject to a dependent attribute.DOI 10.18522/1995-0640-2021-2-113-124